Twin-stack decoding of recursive systematic convolutional codes. - Sivasankaran, R.
We present a method for soft-in/soft-out sequential decoding of recursive systematic convolutional codes. The proposed decoder, the twin-stack decoder, is an extension of the well-known ZJ stack decoder, and it uses two stacks. The use of the two stacks lends itself to the generation of soft outputs, and the decoder is easily incorporated into the iterative ?turbo? configuration. Under thresholded decoding, it is observed that the decoder is capable of achieving near-maximum a posteriori bit-error rate performance at moderate to high signal-to-noise ratios (SNRs). Also, in the iterative (turbo) configuration, at moderate SNRs (above 2.0 dB), the performance of the proposed decoder is within 1.5 dB of the BCJR algorithm for a 16-state, R=1/3, recursive code, but this difference narrows progressively at higher SNRs. The complexity of the decoder asymptotically decreases (with SNR) as 1/(number of states), providing a good tradeoff between computational burden and performance. The proposed decoder is also within 1.0 dB of other well-known suboptimal soft-out decoding techniques
Keywords: BCJR algorithm; MAP BER performance; SNR; Bit-error rate performance; Concatenated coding; Decoder complexity; Iterative decoding; Iterative turbo configuration; Recursive systematic convolutional codes; Signal-to-noise ratios; Soft outputs; Soft-in/soft-out sequential decoding; Suboptimal soft-out decoding; Thresholded decoding; Twin-stack decoding